The Implementation of Total Physical Response (TPR) Method in Improving Arabic Speaking Skills - Pahri, P. (Universitas Muhammadiyah Sumatera Barat, 2021)
Students in Islamic boarding schools have difficulty expressing their thoughts verbally using Arabic. Meanwhile, in terms of understanding written texts and reading written language, they have pretty good skills. This study aimed to describe the implementation of the TPR method to improve the speaking skills. This study used a qualitative method with a descriptive approach. The data were obtained through observation, interviews, and documentation studies. The subjects of this study were Arabic teachers and selected students using the snowball technique. Based on the results, the TPR method can break the ice of communicating in Arabic among students, their difficulties in expressing their thoughts can be minimized by getting used to responding to those around them.